2014
DOI: 10.1016/j.tranpol.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The potential of future aircraft technology for noise and pollutant emissions reduction

Abstract: The negative external impacts of aviation are currently under unprecedented scrutiny. In response, a number of studies into future prospects for improvement have recently been carried out. This paper reviews these studies and discusses their combined implications for emissions of carbon dioxide, oxides of nitrogen, and noise. The results are also compared with targets for emissions reduction proposed by ACARE and NASA. It is concluded that significant future gains are achievable, but not to the extent implied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 11 publications
0
48
0
1
Order By: Relevance
“…However, both IATA and NASA studies have concluded that the technology development alone cannot reach the desired emission reduction goals; novel aircraft concepts needs to be developed to achieve the target aircraft performance. Graham et al [5] from University of Cambridge have summarized different novel aircraft concepts proposed by aviation research communities and have concluded that ACARE and NASA emission goals cannot be achieved without developing transformational concepts. To support this claim, the historical development of commercial aircraft fuel efficiency since 1980 is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, both IATA and NASA studies have concluded that the technology development alone cannot reach the desired emission reduction goals; novel aircraft concepts needs to be developed to achieve the target aircraft performance. Graham et al [5] from University of Cambridge have summarized different novel aircraft concepts proposed by aviation research communities and have concluded that ACARE and NASA emission goals cannot be achieved without developing transformational concepts. To support this claim, the historical development of commercial aircraft fuel efficiency since 1980 is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…According Williams (2007); Parker [61]; Graham et al [24] and Miyoshi and Ibáñez [55] the technological advancement has resulted in a positive trend of fuel efficiency. ATD was measured from engine efficiencies, aerodynamic efficiencies, and structural efficiencies [4,51].…”
Section: Aircraft Technology and Designmentioning
confidence: 99%
“…SEM is a handy statistical tool for evaluating the whole set of relationships among the latent constructs that are indicated by multiple measures defining a research model and for differentiating between the indirect and direct relationships between the latent constructs [24,73,79].…”
Section: Techniques Of Data Analysismentioning
confidence: 99%
“…may come on the market in the next 20 to 40 years with up to 70% reduction in fuel consumption when compared to conventional (tube-and-wing) aircraft (Graham et al, 2014).…”
mentioning
confidence: 99%
“…Some of these future aviation technologies are still in small scale development phase and it's highly unlikely that commercial companies will research these projects without government assistance (Graham et al, 2014). Apart from saving fuel, these future technologies must meet other requirements and regulations such as noise, emissions, scalability, and emergency evacuation and gate size before entering service.…”
mentioning
confidence: 99%